Evaluation of four-wheel vehicle driven by lower limb with electric pedalling assistance for elderly people / Hokyoo Lee ... [et al.] - Hokyoo, Lee; Ab Patar, Mohd Nor Azmi; Takashi, Komeda; Mahmud, Jamaluddin; Yoshiyuki, Takahashi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The idea of designing independent personalized mobility equipment for elderly is to improve the quality of life and improvised the care prevention system in the society. We proposed and designed a four-wheel type of electric power assistant for personal mobility in care prevention. The preliminary experiment was conducted consisted of twenty healthy elderly people (8 males and 12 female) recruited subjects to evaluate the performance of our mobile support equipment system. We examined the change of the physical workload with oxygen uptake amongst healthy subjects. The physical workload is recommended according to protocol suggested in exercise therapy. The purpose of our pilot study is to evaluate the relationship of elderly people specifically for physical workload with the oxygen uptake rate in the different tilted level of the surface route such as on a flat and 8% slope surface route. Although all of recruited subjects were able to safely travel on the flat surface route, yet three subjects interrupted the experiment because of their physical discomfort at 8% slope surface route. Maximum uptake of oxygen when running on the flat surface route with constant speed of 6 km/h travelled distance 1.2 km took durations of 12 minutes 30 seconds not indicated any significant difference in A mode and N mode. Our designed vehicle quantitatively presented the smooth traveling behaviour as possible with less physical workloads on the recruited subjects, even in the 8% slope surface route when using assisted force mode (A mode).Our mobility support equipment is beneficial as a daily outdoor support equipment for the elderly people who have deteriorated in gait function and people with motor impairment due to cerebrovascular disorder.